Analisis Wacana Kritis Pemberitaan Kasus Penipuan di Media Online Kompas.com - Haryadi Mujianto; Heri Hendrawan; Hilyatu Sadiyah (Universitas Garut, 2023)
This research is motivated by the emergence of influencer news that is currently busy in the media audience. One of them is the online media kompas.com which continuously reports on the context of the news. The purpose of this research is to find out the dimensions of the text, discursive practices and socio-cultural practices featured in the reporting on the Doni Salmanan case on kompas.com. The research method used is descriptive qualitative using the theory of Critical Discourse Analysis model of Norman Fairclough as the basis for knowing the microstructural, mesostructural and macrostructural elements displayed in news texts. Data collection techniques were carried out, namely interviews, literature study and documentation. By including news writers and kompas.com editors from the object of analysis as informants. The results of the study show that the aspect of the text dimension in sentence representation displays an event that occurred to Doni Salmanan's influencer related to a trading fraud case. The relations shown by journalists show support for news participants by using direct sentences from news participants supported by indirect sentences from statements from journalists. The culture that occurs is high public interest in information related to criminal cases and celebrities and virality, so that is one of the reasons for the appearance of Doni Salmanan's news on kompas.com. At the situational level, Kompas.com journalists are journalists stationed at the National Police Headquarters so that news is dominated by police statements.